1999
DOI: 10.1103/physrevb.60.4342
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties ofβ(ET)2SF5

Abstract: We report the polarized infrared and optical reflectance of ␤Љ-(ET) 2 SF 5 CH 2 CF 2 SO 3 as a function of temperature. This fully organic superconductor displays weakly metallic behavior over the entire temperature range of our investigation. The electronic properties present several unusual features including the lack of a conventional free carrier ͑Drude͒ response at low temperature, infrared localization phenomena, and an unexpected temperature dependence of the oscillator strength. Similar behavior is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
32
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…It reveals a shoulder at 4800 cm-l and a strong electronic band around 9500 cm '1 [5]. These features are not observed in the spectrum of the superconductor or the metal [6,7]. At the same time, the lb spectra of the sttperconductor and metal are very similar.…”
Section: Introductionmentioning
confidence: 50%
“…It reveals a shoulder at 4800 cm-l and a strong electronic band around 9500 cm '1 [5]. These features are not observed in the spectrum of the superconductor or the metal [6,7]. At the same time, the lb spectra of the sttperconductor and metal are very similar.…”
Section: Introductionmentioning
confidence: 50%
“…It is in fact observed that in a large number of bad metals the Drude peak in the optical conductivity moves away from ω = 0 as the temperature is increased, leading to a suppression of low frequency spectral weight. This phenomenon is seen in ruthenates [16,17], cobaltates [18,19], cuprates [20][21][22][23][24], vanadates [25,26], manganates [27,28], nickelates [29] and organic conductors [30,31]. The behavior is illustrated in figure 1 below.…”
mentioning
confidence: 93%
“…This finding is in qualitative agreement with experimental data on and ␤Љ organic salts. [11][12][13][14] Our results are relevant to the optical response of sodium vanadates, such as ␤-Na 0.33 V 2 O 3 , which also display charge ordering.…”
mentioning
confidence: 93%
“…In particular, the optical conductivity spectra display a broad midinfrared band and the near absence of a Drude-like peak. 11 This is in contrast to conventional metals, for which the total spectral weight is dominated by a Drude peak.…”
mentioning
confidence: 94%